Incidence and management of ureteric stricture in renal transplantation: A local center with ten years of experience - Akram Mahmud (Zanco Journal of Medical Sciences)
Background and objective: Renal transplantation for patients with end-stage renal disease gives better long-term survival results and a better quality of life in comparison with maintenance dialysis. However, some general and urological complications may occur following kidney transplantation. One of those complications is ureteral stricture, but the harm of renal transplant can be avoided when treated in an accurate and timely manner. This study is carried out to determine the incidence of ureteral stricture of renal transplantation, and to appropriately diagnose and treat the conditions.